Beef Demand Determinants: A Research Summary - Schroeder, Ted C.; Marsh, Thomas L.; Mintert, James (My University, 2000)
This publication describes beef demand and how the beef demand changes.
MF2457_2000_03
Keywords: MF2457; Economics; Livestock; MF